2020
DOI: 10.3390/ma13092195
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Antiresonant Oxide Island on the Lasing of Lateral Modes in VCSELs

Abstract: Use of antiresonant structures is a proven, efficient method of improving lateral mode selectivity in VCSELs. In this paper, we analyze the impact of a low-refractive antiresonant oxide island buried in a top VCSEL mirror on the lasing conditions of lateral modes of different orders. By performing comprehensive thermal, electrical, and optical numerical analysis of the VCSEL device, we show the impact of the size and location of the oxide island on the current-crowding effect and compute threshold currents for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…For low island sizes, the modes have a tendency to focus on the high-effective-index region outside its radius, while with larger islands they are confined within it. Later, we have shown that the threshold currents of an electrically pumped device shows the same behavior [36] and its origin closely related to the oscillations of the optical losses and is only weakly modified by the overlap of the optical mode and pumping current profile.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…For low island sizes, the modes have a tendency to focus on the high-effective-index region outside its radius, while with larger islands they are confined within it. Later, we have shown that the threshold currents of an electrically pumped device shows the same behavior [36] and its origin closely related to the oscillations of the optical losses and is only weakly modified by the overlap of the optical mode and pumping current profile.…”
Section: Introductionmentioning
confidence: 79%
“…2. This VCSEL, based on gallium arsenide, was previously analyzed in our work [36]. The resonant cavity is tailored to the freespace wavelength of 850 nm and boasts a length of 3 /2 λ.…”
Section: Lateral Modes Threshold Discriminationmentioning
confidence: 99%
See 3 more Smart Citations